miR-6869-5p Transported by Plasma Extracellular Vesicles Mediates Renal Tubule Injury and Renin-Angiotensin System Activation in Obesity - Liu, Huan-Huan; Li, Xia-Qing; Liu, Jin-Feng; Cui, Shuang; Liu, Han; Hu, Bo; Huang, Si-Bo; Wang, Li; Yang, Wah; Wang, Cun-Chuan; Meng, Yu (Frontiers in Medicine, 2021)
Obesity increases the risk of other diseases, including kidney disease. Local renal tubular renin-angiotensin system (RAS) activation may play a role in obesity-associated kidney disease. Extracellular vehicles (EVs) transmit necessary information in obesity and cause remote organ damage, but the mechanism is unclear. The aim of the study was to investigate whether the plasma EVs cargo miR-6869-5p causes RAS activation and renal tubular damage. We isolated plasma EVs from obese and lean subjects and analyzed differentially-expressed miRNAs using RNA-seq. Then, EVs were co-cultured with human proximal renal tubular epithelial cells (PTECs) in vitro. Immunohistochemical pathology was used to assess the degree of RAS activation and tubule injury in vivo. The tubule damage-associated protein and RAS activation components were detected by Western blot. Obesity led to renal tubule injury and RAS activation in humans and mice. Obese-EVs induce RAS activation and renal tubular injury in PTECs. Importantly, miR-6869-5p-treated PTECs caused RAS activation and renal tubular injury, similar to Obese-EVs. Inhibiting miR-6869-5p decreased RAS activation and renal tubular damage. Our findings indicate that plasma Obese-EVs induce renal tubule injury and RAS activation via miR-6869-5p transport. Thus, miR-6869-5p in plasma Obese-EVs could be a therapeutic target for local RAS activation in obesity-associated kidney disease.